Pengaruh Yoga Asanas Terhadap Penurunan Derajat Skoliosis Di Udana Yoga Bali - Putu Reny Rahmawati; I Made Sugata; I gusti Made Widya Sena (UHN IGB Sugriwa Denpasar, 2023)
Scoliosis is a musculoskeletal disorder that is described by the bending of the spine. Scoliosis also began to be realized in adolescence during the physical and psychological growth period. Choosing the right alternative for dealing with scoliosis is a very important thing, before the degree of spinal curvature getting bigger. One of alternative to deal with scoliosis that is now in demand by the community is by doing special yoga exercises therapy for scoliosis patients at Udana Yoga Bali. In this study, there were several problem formulations, including: (1) Does the practice of yoga asana affect scoliosis patients in Udana Yoga? (2) What is the effect of Yoga Asana at Udana Yoga in decreasing the degree of scoliosis? (3) What is the structure of Yoga Asana practice for scoliosis patients in adolescents at Udana Yoga? To solve the problem formulation, researchers used the Wilcoxon computation technique through SPSS. The aim of this research is to prove scientifically that Yoga Asana practice can have an effect in reducing the degree of scoliosis. This research used quantitative methods with purposive sampling technique in determine the sample data. The results of the statistical test output in this study showed value 0.001 which proved that yoga asanas had an effect on decreasing the degree of scoliosis in adolescents. While the results of testing the effect size were 0.882, which indirectly also provide the conclusion that yoga asanas have high effectiveness toward the decrease of the degree in scoliosis.